2020
DOI: 10.1111/jcmm.15763
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 contributes to the damage of cartilage and subchondral bone in discectomy‐induced TMJOA mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…Meanwhile, the role of innate immune system in the progression of OA has also received increasing attention. Some studies suggested that the innate immune system is an active participant in synovial inflammation and cartilage catabolism and can initiate a series of molecular mechanisms to repair and reverse the damage 40,41 . Two modules were identified in these co‐targeted genes, and the KEGG pathway enrichment analysis results of these two modules both included the TLR and TNF signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the role of innate immune system in the progression of OA has also received increasing attention. Some studies suggested that the innate immune system is an active participant in synovial inflammation and cartilage catabolism and can initiate a series of molecular mechanisms to repair and reverse the damage 40,41 . Two modules were identified in these co‐targeted genes, and the KEGG pathway enrichment analysis results of these two modules both included the TLR and TNF signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that the innate immune system is an active participant in synovial inflammation and cartilage catabolism and can initiate a series of molecular mechanisms to repair and reverse the damage. 40 , 41 Two modules were identified in these co‐targeted genes, and the KEGG pathway enrichment analysis results of these two modules both included the TLR and TNF signalling pathway. Previous research suggested that synovial inflammation can affect the cartilage innate immune system through TLR4/MyD88 signalling pathway, induce cartilage inflammation and degeneration and then aggravate the OA process.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17, IL-1β and TNF-α expressed by synovial cells induce the RANKL expression in synovial fibroblasts and osteoblasts, promoting osteoclast formation and bone resorption [ 16 ]. Toll-like receptor 4 (TLR4), which mediates the innate immune reaction, aggravates the damage of cartilage and subchondral bone in discectomy-induced TMJ OA through activation of MyD88/NF-κB pathway in mice [ 17 ]. In addition, inflammatory cytokines are also in close correlation with pain in TMJ OA.…”
Section: Tmj Oa: Pathogenesismentioning
confidence: 99%
“…It has been shown that expression of TLR4 and NF-κB was elevated in the synovium in TMJ OA patients and in discectomy-induced TMJ OA in mice. TLR4 was also elevated in the damaged cartilage and subchondral bone through activation of MyD88/NF-κB [ 17 ]. It has been shown that the cartilage degeneration of TMJ OA can be inhibited by blocking the periostin–NF–κB-ADAMTS5 pathway [ 76 ].…”
Section: Molecular Signaling During Tmj Oa Developmentmentioning
confidence: 99%
“…It can cause structural damage and abnormal articular forces to induce OA-like lesions directly by using surgical and mechanical devices. The common surgical methods include discectomy ( Hinton, 1992 ; Lan et al, 2017 ; Liu X. et al, 2020 ; Saito et al, 2021 ), partial discectomy ( Man et al, 2009 ; Xu et al, 2009 ; Lei et al, 2022 ), disc perforation ( Embree et al, 2015 ; Luo et al, 2020 ; Ruscitto et al, 2020 ), anterior disc displacement ( Togni et al, 2018 ; Xu et al, 2018 ; Nguyen et al, 2020 ), injury of the condylar surface ( Ishimaru and Goss, 1992 ; Wang F. et al, 2017 ), and postero-superior displacement of the mandible ( Imai et al, 2001 ; Liu et al, 2006 ) ( Table 3 ). These six methods well mimic advanced symptoms of joint injury in clinical patients, but they are not starting factors in general TMJOA.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%